Balanced polymorphisms and their divergence in a Heliconius butterfly. Issue 24 (8th December 2021) - Ogilvie, James G.; Van Belleghem, Steven; Range, Ryan; Papa, Riccardo; McMillan, Owen W.; Chouteau, Mathieu; Counterman, Brian A.
Abstract: The evolution of mimicry in similarly defended prey is well described by the Müllerian mimicry theory, which predicts the convergence of warning patterns in order to gain the most protection from predators. However, despite this prediction, we can find great diversity of color patterns among Müllerian mimics such as Heliconius butterflies in the neotropics. Furthermore, some species have evolved the ability to maintain multiple distinct warning patterns in single populations, a phenomenon known as polymorphic mimicry. The adaptive benefit of these polymorphisms is questionable since variation from the most common warning patterns is expected to be disadvantageous as novel signals are punished by predators naive to them. In this study, we use artificial butterfly models throughout Central and South America to characterize the selective pressures maintaining polymorphic mimicry in Heliconius doris . Our results highlight the complexity of positive frequency‐dependent selection, the principal selective pressure driving convergence among Müllerian mimics, and its impacts on interspecific variation of mimetic warning coloration. We further show how this selection regime can both limit and facilitate the diversification of mimetic traits. Abstract : The selective pressures maintaining polymorphism among Müllerian mimics are relatively unknown. Here, we use artificial butterfly models to characterize how regional differences in predation pressures can both drive and dissuade the evolution of warning color patterns in Heliconius butterflies.